Exploring the synthesis, structure, spectroscopy and biological activities of novel 4-benzylidene-1-(2-(2,4-dichloro phenyl)acetyl) thiosemicarbazide derivatives: An integrated experimental and theoretical investigation - Mahnoor Waheed; Sana Idris; Faheem Jan; Aftab Alam; Aftab Alam; Muhammad Ibrahim; Abdullah F. AlAsmari; Metab Alharbi; Fawaz Alasmari; Momin Khan (Elsevier, 2023)
Background: Novel α-amylase inhibitors play a crucial role in managing diabetes and obesity, contributing to improved public health by addressing these challenging and prevalent conditions. Moreover, the synthesis of anti-oxidant agents is essential due to their potential in combating oxidative stress-related diseases and promoting overall health. Objective: Synthesis of thoisemicarbazone derivatives of 2,4-dichlorophenyl acetic acid and to screened them for their biological activities. Method: Thiosemicarbazone derivatives (4-13) were synthesized by refluxing 2,4-dichlorophenyl acetic acid with sulfuric acid in ethanol to get the ester (2), which was further refluxed with thiosemicarbazide to get compound (3). Finally, different aromatic aldehydes were refluxed with compound (3) in ethanol in catalytic amount of acetic acid to obtained the final products (4-13). Using modern spectroscopic techniques including HR-ESI-MS, 13C-, and 1H NMR, the structures of the created derivatives were confirmed. Results: The synthesized derivatives showed excellent to good inhibitory activity in the range of IC50 values of 4.95 ± 0.44 to 69.71 ± 0.05 µM against α-amylase enzyme when compared to standard drug acarbose (IC50 = 21.55 ± 1.31 µM). In case of iron chelating activity, these products showed potent activity better than standard EDTA (IC50 = 66.43 ± 1.07 µM) in the range of IC50 values of 22.43 ± 2.09 to 61.21 ± 2.83 µM. However, the obtained products also show excellent to good activity in the range of IC50 values of 28.30 ± 1.17 to 64.66 ± 2.43 µM against hydroxyl radical scavenging activity when compared with standard vitamin C (IC50 = 60.51 ± 1.02 µM). DFT used to calculate different reactivity factors including ionization potential, electronegativity, electron affinity, chemical softness, and chemical hardness were calculated using frontier molecular orbital (FMO) computations. The molecular docking studies for the synthesized derivatives with α-amylase were carried out using the AutoDock Vina to understand the binding affinities with active sites of the protein.